New carboxamide derivatives bearing benzenesulphonamide as a selective COX-II inhibitor: Design, synthesis and structure-activity relationship - Ugwu, David Izuchukwu; Okoro, Uchechukwu Chris; Ahmad, Hilal (PLOS ONE, 2017)
Sixteen new carboxamide derivatives bearing substituted benzenesulphonamide moiety (7a-p) were synthesized by boric acid mediated amidation of appropriate benzenesulphonamide with 2-amino-4-picoline and tested for anti-inflammatory activity. One compound 7c showed more potent anti-inflammatory activity than celecoxib at 3 h in carrageenan-induced rat paw edema bioassay. Compounds 7g and 7k also showed good anti-inflammatory activity comparable to celecoxib. Compound 7c appeared selectivity index (COX-2/COX-1) better than celecoxib. Compound 7k appeared selectivity index (COX-2/COX-1) a little higher than the half of celecoxib while compound 7g is non-selective for COX-2. The LD50 of compounds 7c, 7g and 7k were comparable to celecoxib.